Homicidal Physical Violence: An Exploratory Analysis of Relevant Cognitive, Demographic, and Criminological Factors in a Sample of Murderers - Mazurek, Callie (Homicide studies, 2021)
Homicide injury severity (HIS), the degree of physical injury inflicted on a victim during a homicide, has emerged as a relevant criminological variable. However, little is known regarding the offender characteristics and criminological variables that may be associated with greater HIS. Data (demographic, cognitive, and criminological variables) from forensic neuropsychological evaluations of N = 101 offenders convicted of murder, were explored in relation to the Homicide Injury Scale. Numerous factors were related to HIS. Results partially replicate prior findings of factors associated with violent offending and provide preliminary evidence for distinct risk factors for inflicting severe injury during a homicide.